The Determinants of Transfer Pricing in Multinational Companies - Devita, Hanik; Solikhah, Badingatus (Universitas Negeri Semarang, 2021)
This study aims to examine the effect of tunneling incentives, institutional ownership, exchange rates, profitability, and leverage on companies’ decisions to transfer pricing to multinational companies. The population in this study is multinational companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The purposive sampling method is used as a sampling technique obtained by 60 companies or 272 units of analysis as the object of observation. Data collection techniques using documentation techniques with secondary data sourced from financial reports. The data analysis technique used panel data regression. The results of this study prove that institutional ownership and leverage have a significant positive effect on transfer pricing. Tunneling incentives and profitability do not affect transfer pricing. However, the exchange rate has a significant negative effect on transfer pricing. The conclusion of this research is that transfer pricing will increase if institutional ownership and leverage are high. Meanwhile, transfer pricing will decrease if the exchange rate increases. However, transfer pricing is not influenced by tunneling incentives and profitability. Multinational companies can increase profitability and institutional ownership by paying attention to exchange rates and reducing tunneling incentives and leverage in order to generate greater corporate profits and minimize transfer pricing practices. Keywords: Tunneling Incentive; Institutional Ownership; Exchange Rate; Profitability; Leverage